2015
DOI: 10.4238/2015.december.29.9
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane downregulates interleukin-6 and interleukin-8 levels in patients after cardiopulmonary bypass surgery: a meta-analysis

Abstract: ABSTRACT. This study aimed to investigate the effect of sevoflurane on serum levels of interleukin (IL)-6 and IL-8 in patients who underwent cardiopulmonary bypass (CPB). The strength of the association between sevoflurane treatment and serum level of IL-6 and IL-8 was determined in patients who underwent CPB by summary standard mean differences (SMDs); 95% confidence interval (CI) was used. In total, seven casecontrol studies showed decreased IL-6 and IL-8 levels in sevofluranetreated patients than in control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…KCNK2 (potassium channel subfamily K member 2) is targeted by five inhalational anesthetic agents. These agents have antiinflammatory effects both systemically 61 and in the lungs 62 and meta-analysis of clinical studies shows protection against pulmonary complications after cardiac surgery 63 . A recent trial suggested that one of these inhalation agents, sevoflurane, offers promise for reducing epithelial injury and improving outcomes in patients with acute respiratory distress syndrome 64 .…”
Section: Discussionmentioning
confidence: 99%
“…KCNK2 (potassium channel subfamily K member 2) is targeted by five inhalational anesthetic agents. These agents have antiinflammatory effects both systemically 61 and in the lungs 62 and meta-analysis of clinical studies shows protection against pulmonary complications after cardiac surgery 63 . A recent trial suggested that one of these inhalation agents, sevoflurane, offers promise for reducing epithelial injury and improving outcomes in patients with acute respiratory distress syndrome 64 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in all of these reports, rats received sevoflurane treatment as early as 2 h after the onset of LPS challenge for another 4 h; time dependent effects of sevoflurane treatment were not examined. Interestingly, a recent meta-analysis of patients who underwent cardiopulmonary bypass showed that serum levels of the pro-inflammatory cytokines IL-6 and IL-8 were significantly decreased in sevoflurane pre- and posttreated patients [ 20 ], supporting the notion that sevoflurane anesthesia inhibits the inflammatory response. In this regard our results add to these findings and show that sevoflurane posttreatment promptly prevents inflammation and oxidative responses, but inhibits lung injury in a time dependent manner during mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Because many injurious events take place before treatment is available, from a clinical aspect, it would be interesting to know whether inhaled anesthetics act protectively when applied ex post. In fact, the organ-protective effects of sevoflurane or isoflurane posttreatment were demonstrated for patients receiving a cardiopulmonary bypass [ 20 ], as well as for several other experimental injury models [ 14 , 15 , 21 26 ]. For instance, sevoflurane posttreatment protected rats from cerebral ischemia-reperfusion injury [ 14 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, sevoflurane administration may reduce inflammatory markers. In a recent meta-analysis of patients undergoing coronary artery bypass grafting (CABG) surgery, sevoflurane pretreatment significantly reduced concentrations of the pro-inflammatory cytokines interleukin (IL)-6 and IL-8 compared with controls [ 79 ].…”
Section: Emerging Topics In Inhalation Anesthesiamentioning
confidence: 99%